Injury analysis of a professional female soccer team in first division Italian season - Pellegrini, A.; Lombardi, M.; Riva, N.; Combi, F.; Pecci, C.; Porcellini, G. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Soccer, the most popular sport worldwide, has seen an exponential increase in women`s participation at the elite level in the last few years. The main purpose of the current epidemiological study was to analyze the injury incidence, characteristics, and burden among elite female soccer players during a regular season. METHODS: We recorded all injuries that occurred throughout the 2018-2019 competitive soccer season (August-April). The studied group consisted of 22 elite players, who were militant in the first national leagues from the first team of the same soccer club in the north of Italy. The 2006 FIFA consensus statement was used to design the injury registration form. RESULTS: Throughout the 2018-2019 season, medical staff treated 35 injuries in 22 females. Of the total number of injuries reported in 9 months (5.8 injuries per 1000 hours of exposure), 7 (20%) occurred during matches and 28 (80%) during training sessions. The most common injury was represented by muscular disorders (18; 51.43%) which affected the thigh in 16 cases, and the lower leg and trunk in one case each. According to an anatomic site, most injuries occurred in the lower limbs (94,28%), with the majority affecting thighs (16; 45%), ankles (8; 23%), and knees (5; 14%). CONCLUSIONS: Non-contact injuries are shown to be more frequent than contact injuries, which may be connected to the increasing athletic burden among athletes. Further prospective investigations are needed with a focus on prevention protocols.